Peningkatan produktivitas padi gogo melalui inovasi teknologi pertanian menuju swasembada pangan nasional di Desa Pollewani, Kabupaten Polewali Mandar - HM., Rahmaniah; Syah, Ikrar Taruna; Utami, Rahmawati Ning; Khaerati, Rahma; Aswad, Muhammad; Arsyad, Muhammad; Haris, Abd. (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2025)
Pollewani Village is one of the areas in Tutar District, Polewali Mandar Regency, which has the largest and most remote administrative area in the regency, and therefore receives less attention from the regency government. This area has significant potential for dryland rice, with productivity reaching 3.97 tons per hectare in 2023. However, this yield is still much lower than that of wetland rice, corn, and cassava in the area. One solution to this problem is technological innovation, primarily through farmer training and the provision of modern facilities and infrastructure. By improving farmers' skills in dryland rice cultivation and introducing new superior varieties of rice seeds (Inpari-32), it is hoped that this will support the rate of increase in upland rice production in Pollewani Village. The implementation method includes providing interactive materials, practice in demonstration plots, and evaluation using questionnaires. The results indicate that this activity can increase farmers' knowledge, as evidenced by an increase in participants' average score from 33.33 to 70.